Contemporary antiplatelet treatment in acute coronary syndrome patients undergoing percutaneous coronary intervention: 1‐year outcomes from the GReek AntiPlatElet (GRAPE) Registry. (4th May 2016) - Alexopoulos, D.; Xanthopoulou, I.; Deftereos, S.; Hamilos, M.; Sitafidis, G.; Kanakakis, I.; Pentara, I.; Vavouranakis, M.; Davlouros, P.; Hahalis, G.; Goudevenos, J.
Abstract : Essentials The comparative efficacy and safety of antiplatelet agents in 'real life' is not clear. We recruited acute coronary syndrome patients receiving percutaneous coronary intervention. At 1‐year follow‐up, prasugrel offers better anti‐ischemic protection than clopidogrel. Prasugrel and ticagrelor are accompanied by more frequent bleeding events. Summary: Background: The comparative efficacy and safety of antiplatelet treatment outside randomized trials is not clear. Objectives: To investigate long‐term efficacy and safety in 'real‐life' acute coronary syndrome (ACS) patients treated by percutaneous coronary intervention (PCI) with contemporary use of clopidogrel, prasugrel and ticagrelor. Methods: In a prospective, observational, multicenter cohort study, 2047 patients were recruited into the GReek AntiPlatElet (GRAPE) Registry and were followed‐up for 1 year for major adverse cardiovascular events (MACE, a composite of death, non‐fatal myocardial infarction, urgent revascularization and stroke) and bleeding events (Bleeding Academic Research Consortium [BARC] classification). Results: Exposure to clopidogrel, prasugrel and ticagrelor by PCI occurred in 959, 363 and 717 patients, respectively. After adjustment, the rate of MACE (primary outcome endpoint) was lower in prasugrel‐treated patients (4.4%) than in clopidogrel‐treated patients (10.1%) (hazard ratio [HR], 0.53; 95% confidence interval [CI], 0.30–0.91), although not significantly different between ticagrelor (6.8%) and clopidogrel groups (HR, 0.78; 95% CI, 0.54–1.12). Any type of BARC‐classified bleeding (secondary outcome endpoint) was more frequent in prasugrel‐treated patients (51.2%) than in clopidogrel‐treated patients (37.6%) (HR, 1.61; 95% CI, 1.33–1.95) and more frequent in ticagrelor‐treated patients (56.9%) than in clopidogrel‐treated patients (HR, 1.81; 95% CI, 1.55–2.10). An adjusted comparison between prasugrel and ticagrelor‐treated groups did not reveal differences in any outcome measure. After adjustment, the death rate was more reduced by novel agents in comparison with clopidogrel (2.9% vs. 6.2%). Conclusions: In ACS/PCI patients, prasugrel offered better anti‐ischemic protection than clopidogrel, whereas use of both novel agents is accompanied by more frequent bleeding events.